2003
DOI: 10.1016/s0168-9002(02)01895-8
|View full text |Cite
|
Sign up to set email alerts
|

Fundamental limits of positron emission mammography

Abstract: We explore the causes of performance limitation in positron emission mammography cameras. We compare two basic camera geometries containing the same volume of 511 keV photon detectors, one with a parallel plane geometry and another with a rectangular geometry. We find that both geometries have similar performance for the phantom imaged (in Monte Carlo simulation), even though the solid angle coverage of the rectangular camera is about 50% higher than the parallel plane camera. The reconstruction algorithm used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 19 publications
0
14
0
Order By: Relevance
“…In comparison the CYBPET with two parallel planes, the CYBPET has more sensitivity because of its whole 3601 coverage that will reduce the scan time (or increase patient frequency) and or the injected dose which can compensate the increased price of CYBPET in a duration of time. Furthermore, it has been shown that [28] the images from the parallel plane PEM will suffer from some blurring or degraded spatial resolution, because of the large gap in the angular coverage.…”
Section: Resultsmentioning
confidence: 99%
“…In comparison the CYBPET with two parallel planes, the CYBPET has more sensitivity because of its whole 3601 coverage that will reduce the scan time (or increase patient frequency) and or the injected dose which can compensate the increased price of CYBPET in a duration of time. Furthermore, it has been shown that [28] the images from the parallel plane PEM will suffer from some blurring or degraded spatial resolution, because of the large gap in the angular coverage.…”
Section: Resultsmentioning
confidence: 99%
“…Focal Plane Tomography (FPT) is one of the algorithms that can be used in PEM for image reconstruction [8]. This method consists in finding the positions of intersection between the lines of response (LOR's) within the field of view (FOV) of the scanner and what it is called a "focal plane".…”
Section: Depth-of-interaction and Image Reconstructionmentioning
confidence: 99%
“…Positron emission mammography (PEM) systems consist of two parallel detectors that do not rotate, and these provide slice data parallel to detectors using focal plane tomographic techniques (or limited-angle tomography) (Fig. 24) [86,87]. Usually, the breasts are compressed by the detector head to spread out breast tissues and provide a view similar to that of X-ray mammography [88].…”
Section: Breast-dedicated Positron Imaging Systemsmentioning
confidence: 99%
“…The shortcomings of these PEM systems using focal plane tomography that received most attention are the significant image blurring that occurs along the axis perpendicular to the detector plane and the broad background noise, which reduces image contrast [21,89]. Although an iterative reconstruction algorithm that provides accurate modeling of statistical noise and detector response was devised to solve the above problems due to limited angular coverage of PEM systems with two parallel detectors, convergence required several hours depending on data size [87]. Widening the angular coverage by rotating the planar detectors or utilizing a full ring or rectangular camera geometry provide the most direct ways of coping with the limitations of limited-angle tomography and of providing isotropic resolution in all three dimensions.…”
Section: Breast-dedicated Positron Imaging Systemsmentioning
confidence: 99%